Protocol for a Delphi consensus study to identify priority characteristics of integrated care for individuals with severe mental illness and comorbid physical disorders in Europe - Esther Touitou-Burckard; Tomasz Gondek; Ulker Isayeva; René Ernst Nielsen; Heidi Taipale; Jari Tiihonen; Laurent Boyer; Coralie Gandré (PLoS ONE, 2026)
Introduction Individuals with severe mental illness (SMI) experience persistent and complex physical health needs that remain insufficiently addressed. While integrated care represents a promising solution, there is no consensus among stakeholders regarding what constitutes best-practice organizational models for this population. As part of the European Mental and Physical Health Initiative for People with Severe Mental Disorders (EU-MIND), this study aims to identify expert consensus on the key characteristics of integrated care models for individuals with SMI to support their sustainable implementation across Europe. Methods This study will use an online Delphi process, with up to three rounds, to engage stakeholders from six European countries (Denmark, Finland, France, Italy, Poland, and Sweden). Participants will include people living with SMI, their relatives, health and care professionals, public decision-makers and institutional actors with relevant experience related to the research topic. A minimum sample size of 33 participants per country will be targeted, with the aim of ensuring balanced representation across the different categories of participants. They will be asked to rate the importance of potential key characteristics of integrated care models using Likert scales. A characteristic will be considered to have reached consensus if more than 70% of the respondents agree on its degree of importance. This study complies with the Delphistar reporting guidelines for Delphi studies and has received ethical approval from the Aix-Marseille University Ethics Committee and the Swedish Ethical Review Authority. Discussion This study will provide expert-based guidance on the core characteristics of integrated care for individuals living with SMI. By capturing diverse stakeholder perspectives across countries and healthcare systems, it will help define shared priorities and inform future service design, implementation and policy, supporting sustainable and context-sensitive care development in Europe.